Testing the effectiveness of the Developing Inclusive Youth program: A multisite randomized control trial. Issue 3 (25th May 2022) - Killen, Melanie; Burkholder, Amanda R.; D'Esterre, Alexander P.; Sims, Riley N.; Glidden, Jacquelyn; Yee, Kathryn M.; Luken Raz, Katherine V.; Elenbaas, Laura; Rizzo, Michael T.; Woodward, Bonnie; Samuelson, Arvid; Sweet, Tracy M.; et al.
Abstract: The Developing Inclusive Youth program is a classroom‐based, individually administered video tool that depicts peer‐based social and racial exclusion, combined with teacher‐led discussions. A multisite randomized control trial was implemented with 983 participants (502 females; 58.5% White, 41.5% Ethnic/racial minority; M age  = 9.64 years) in 48 third‐, fourth‐, and fifth‐grade classrooms across six schools. Children in the program were more likely to view interracial and same‐race peer exclusion as wrong, associate positive traits with peers of different racial, ethnic, and gender backgrounds, and report play with peers from diverse backgrounds than were children in the control group. Many approaches are necessary to achieve antiracism in schools. This intervention is one component of this goal for developmental science.